Time for Revitalisation of Value Chain Management: A Reassessment of Porter’s View on Procurement (Global Journal of Management and Business Research, 2022)
In the light of recent disruptive events global supply chains have displayed their vulnerability which has stressed the importance of procurement in modern practice This study aims to analyse if the procurement function can be reconsidered as a primary activity in Porter s 1985 value chain
Keywords: value chain; competitive advantage; inbound logistics; procurement; buyer value; agility; covid-19; suez canal blockage; procurement logistics